Decision-making capacity at the end of life. (June 2015) - Kepple, Alyson L.; Azzam, Pierre N.; Gopalan, Priya; Arnold, Robert M.
<x content-type="archive" xml:space="preserve">Abstract</x> Medical decision-making capacity refers to the assessment of a patient's ability to make a specific clinical choice. Systematic evaluation of capacity includes a review of the core components of decision making, alongside consideration of potential outcomes associated with the choice. At the end of life, assessing capacity may be complicated by drastic shifts in the risk–benefit profile of acute medical interventions, along with changes to a patient's affect, behavior, and cognition. Maintaining an appreciation for the elements of capacity, the process of assessing capacity, and the associated challenges at the end of life can help palliative care clinicians to ensure provision of respectful, patient-centered care. This manuscript provides an overview of decision-making capacity in the palliative care population, while clarifying common barriers to capacity at the end of life, and offering considerations for appropriate involvement of psychiatric consultants in this process.